Design, User Experience, and Usability: Design Thinking and Methods 5th International Conference, DUXU 2016, Held as Part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings, Part I - Marcus, Aaron (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
The three-volume set LNCS 9746, 9747, and 9748 constitutes the proceedings of the 5th International Conference on Design, User Experience, and Usability, DUXU 2016, held as part of the 18th International Conference on Human-Computer Interaction, HCII 2016, in Toronto, Canada, in July 2016, jointly with 13 other thematically similar conferences. The total of 1287 papers presented at the HCII 2016 conferences were carefully reviewed and selected from 4354 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 157 contributions included in the DUXU proceedings were carefully reviewed and selected for inclusion in this three-volume set. The 49 papers included in this volume are organized in topical sections on design thinking; user experience design methods and tools; usability and user experience evaluation methods and tools.